(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SUMARIO: 1. Introducción - 2. Caracteres generales del proyecto de ley: el reconocimiento del matrimonio de creencia - 3. Algunas claves jurídicas de esta nueva propuesta normativa. A New Bill to Recognize the Belief Marriage in England: the Marriage (Approved Organisations) Bill ABSTRACT: In this paper the author briefly examines the content of the Marriage (Approved Organisations) Bill, a proposal recently introduced in the House of Lords, which is aimed to amend the wedding law in England and Wales in order to recognise al last the humanist marriages and, more widely, the marriages of the so called belief bodies that have already been introduced in almost every other jurisdiction in the British Islands, so these new belief marriages can be granted an equivalent status to the one currently conferred to religious marriages.